Stigma of People Affected by Leprosy and its determinants: a cross-sectional study in Sri Lanka - Udhishtran Arudchelvam; Thayaparan Pulendran; Maheshi Sirimanne; Sandali Pabasara; Indira Kahawita; Nadeeka Chandraratne (BMC Infectious Diseases)
Abstract Background Leprosy, being a neglected tropical disease, remains a significant public health concern in several parts of the world, especially Sri Lanka, where it has long been associated with stigma. This study aims to assess the stigma faced by People Affected by Leprosy (PAL) undergoing treatment and to identify the factors associated with this stigma. Methods A cross-sectional study was conducted among 109 Leprosy affected people attending the Central Leprosy Clinic and all dermatology clinics of the National Hospital of Sri Lanka (Colombo), selected using a consecutive sampling method. Data collection was done through an interviewer-administered questionnaire. Stigma was quantified using a validated and adapted version of the Stigma Assessment and Reduction of Impact (SARI) tool, which evaluates stigma pertaining to four domains: Experienced Stigma (ES), Disclosure Concerns (DC), Internalized Stigma (IS), and Anticipated Stigma (AS). Spearman’s correlation and Mann-Whitney U tests were used to analyze associations, with statistical significance set at 0.05. Results The dataset showed a non-normal, right-skewed distribution. The mean total SARI score was 9.82 (SD = 10.23). Disclosure Concerns (rs=-2.66; p = 0.005) and Anticipated Stigma (rs=-3.6; p < 0.001) demonstrated weak - moderate negative correlations with the time since diagnosis. On the other hand, the correlation between time since diagnosis and Experienced Stigma (rs=0.22; p = 0.022) was positive and weak. Participants without disability had significantly lower scores in DC (p = 0.049), IS (p = 0.01), and AS (p = 0.01) compared to those with disability. Patients who did not develop Leprosy reactions displayed significantly lower scores across all SARI domains as well as the total SARI score (all p < 0.05) compared to those who did. Conclusions The findings suggest that over time, People Affected by Leprosy become less concerned about disclosing their diagnosis and anticipate less stigma but may experience greater overall stigma. Disability status and Leprosy reactions are key factors in determining the level of stigma faced by them.